SOCIALIZATION OF ENGINEERING STUDENTS AND FOREIGN LANGUAGE TEACHING - N. K. Ivanova; S. Shishkina (Высшее образование в России)
The paper addresses some vital problems relating to students’ socialization in learning a foreign language at different levels. The authors substantiate the demand for creating an educational environment as integration of teaching, bringing up and socialization as a means of creating student’s cognitive abilities and responsible social conduct. Some examples of successful socio-cultural projects, from the authors’ own experience, are given.